Place branding and product-place image effects - Papadopoulos, Nicolas (Henry Stewart Talks, 2009)
Importance of place and nation branding, and its evolution over time, Place images in business, government and everyday life, The role of images in branding, and of branding and symbolism in perception and marketing, Components and characteristics of place images, Challenges to effective place branding, Main ingredients and strategic approaches to successful branding of places